Physicochemical water quality parameters in typical rice-crayfish integrated systems (RCIS) in China - Yu, Jixin; Ren, Yan; Xu, Tao; Li, Wei; Xiong, Mantang; Zhang, Tanglin; Li, Zhongjie; Liu, Jiashou (International Journal of Agricultural and Biological Engineering, 2018)
To determine the variation of water quality in rice-crayfish (Procambarus clarkii) integrated systems (RCIS) in China, eleven water quality parameters were measured monthly in a typical RCIS located in Qianjiang City (Hubei Province) from July 2014 to June 2015, the parameters were analyzed with principal component analysis (PCA) and compared between the trenches and rice areas during the rice fallow period (Nov-May). The trench and rice area comprehensive results showed that pH (7.48-8.68), NH4+-N (0.2-1.09 mg/L), NO2–N (<0.052 mg/L) and conductivity (435-951 μS/cm) were within the suitable ranges for P. clarkii and that turbidity (TU) was high during the crayfish harvesting and rice planting season. Annual averages of total nitrogen (TN), total phosphorus (TP), permanganate index (CODMn), and chlorophyll a (Chl.a) content were <2 (except in Nov-Dec), 0.25, 10 mg/L, and 50 mg/m3 (especially in Nov-May, <10 mg/m3), respectively. Dissolved oxygen (DO) was below 4 mg/L in Mar-Sep, with a minimum of 1 mg/L, and much higher in Oct-Feb. The maximum and minimum monthly average water temperature (WT) were 31.4°C in July and 5.7°C in December, while the maximum and minimum instantaneous WT were 39.7°C and 2.5°C, respectively . PCA analysis showed that the first three axes, which were mainly correlated with DO, WT and nutrient level, described most information of the parameters, and parameters showed seasonal changes. Some differences were observed in water parameters between the trenches and rice areas, i.e., trenches generally had higher TU, WT and DO, and lower TN, TP and CODMn, although no significant differences were found in some months and some parameters. The study revealed relatively low water nutrient level, probable extreme WT and DO level in some seasons, and certain differences between the trenches and rice areas in typical CRIS in China. Accordingly, some measures should be taken to improve the negative parameters: 1) enhance the water fertility; 2) increase DO, especially in Mar-Sep; 3) increase the trench and water depth to avoid extreme WT. And water quality management should be addressed in both trenches and rice areas. Keywords: rice-crayfish integrated system, co-culture, water quality parameters, trench, rice production area, PCA DOI: 10.25165/j.ijabe.20181103.3761 Citation: Yu J X, Ren Y, Xu T, Li W, Xiong M T, Zhang T L, et al. Physicochemical water quality parameters in typical rice-crayfish integrated systems (RCIS) in China. Int J Agric & Biol Eng, 2018; 11(3): 54–60.